PERAN UNITED NATIONS HIGH COMMISSIONER FOR REFUGEES (UNHCR) DALAM MENANGANI PENGUNGSI YAZIDI DI IRAK (2014-2017) - Megah Cinthya; Yuli Fachri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research explains the role of United Nations High Commissioner for Refugees (UNHCR) in handling Yazidi refugees in Iraq 2014-2017. The UN High Commissioner for Refugees (UNHCR) is one part of the United Nations. UNHCR has a responsibility on humanitarian issues particularly refugee cases because of UNHCR's mandate. In August 2014, extremist Islamic militant groups from the Islamic State of Iraq and Syria (ISIS) killed thousands of Yazidi residents in the Sinjar region of Iraq.The writer uses the pluralism perspective and groupings of countries level of analysis. The theory used for this research is theory of international organization. This research uses qualitative research method. The data was obtained through library research, and search online media research. Further, that was arranged in the form of descriptive research report.UNHCR have a role as the initiator by collaborating with Canada in the resettlement program. As a facilitator, UNHCR provides direct relief facilities to Yazidi refugees, and cooperates with the UN's world food program to provide food aid to Yazidi refugee families who escaped violence and abuse in the Sinjar region. And as a determinator, UNHCR provides refugee status through the refugee status determination mechanism (RSD) based on the 1951 Convention on refugee status. In addition, UNHCR also helps refugees to obtain durable solutions, namely, local integration, voluntary repatriation and resettlement.Keywords : UNHCR, Role, Refugee, Yazidis, International Organization